Influence of Phormidium tenue on Mangrove Seedlings - Kathiresan, K.; Sakthivel, K.; Rajendran, N. (Indian Forester, 2007)
Of the seven species of cyanobacteria isolated from the mangrove sediments, Phormidium tenue exhibited a high ability of fixing nitrogen and hence, this species was tested as biofertilizer to mangrove seedlings of Avicennia marina (Forssk.) Vierh., Ceriops decandra (Griff.) Ding Hou and Aegiceras corniculatum (L.) Blanco. In A. marina, the treatment exhibited higher total biomass by 54.14%, no. of leaves by 48.19% and plant height by 36.83% than in control. In C. decandra, the cyanobacterial treatment enhanced the fresh weight of leaves by 83.12 %. In A. corniculatum, the treatment increased the plant height growth by 10.93 %. Thus the marine cyanobacterium, P. tenue has potential for a biofertilizer to mangroves.